Comparative experimental infection of Lacazia loboi in BALB/c and B10.A mice - Madeira, Suzana; Fernandes Belone, Andrea de Faria; Padovani, Carlos Roberto [UNESP]; Araújo Opromolla, Diltor Vladimir (My University, 2003)
Both hind foot pads of BALB/c and B10.A mice strains, were inoculated with a fungal suspension of Lacazia loboi obtained from a Jorge Lobo's disease patient. The suspension had 9 × 105 cells/ml and its viability index was 45%. The animals were sacrificed at different time periods varying from 24 h to 18 months after inoculation. The BALB/c mice developed an extensive granulomatous infiltrate, similar to the disease in humans, that progressively evolved. The number of fungal elements also increased as the disease progressed, and after the seventh month of inoculation, macroscopic changes of the foot pads were evident. Although the B10.A mice developed an exuberant granulomatous infiltrate, macroscopic changes were not detected. The number of fungal cells in the infected tissues increased in number, but they were lower then the numbers found in the BALB/c strain. The viability indexes were also lower for the B10.A strain. Considering the histopathological findings, the presence of macroscopic changes and the great amount of fungal cells in the infected tissues, the authors concluded that the BALB/c mice strain was more susceptible to L. loboi infection than the B10.A strain.
Keywords: Jorge Lobo's disease; Lacazia loboi; Mouse; animal experiment; cell count; cell infiltration; cell viability; controlled study; experimental infection; foot pad; fungal cell; granuloma; keloidal blastomycosis; mouse; mouse strain; mycosis; nonhuman; Animals; Mice; Mice, Inbred BALB C; Paracoccidioidomycosis; Animalia